2010
DOI: 10.1080/13552600903389452
|View full text |Cite
|
Sign up to set email alerts
|

Much ado about nothing? Representations and realities of online soliciting of children

Abstract: This paper is concerned with where the public's ideas come from about online risks to children and young people. Combining perspectives from criminology, sociology and media studies, it will be argued that as a culture we are confused about childhood and hold on to highly ambiguous ideas about children and sexuality. Further, despite the media's inclination to present adult attraction to children as a uniquely ''modern'' phenomenon, conflicting notions of childhood have always underpinned social and legal norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Grooming is a deceitful process whereby a young person is ill equipped to deduce warning signs (Berson, 2003). Identity is not fixed online, rather is a fluid entity, which can be continually changed and adjusted (Jewkes, 2010), this may increase the chance of a young person engaging with an offender as their suspicions are lowered. Deception often involves the offender masquerading as a young person (Palmer & Stacey, 2004).…”
Section: Deceptionmentioning
confidence: 99%
“…Grooming is a deceitful process whereby a young person is ill equipped to deduce warning signs (Berson, 2003). Identity is not fixed online, rather is a fluid entity, which can be continually changed and adjusted (Jewkes, 2010), this may increase the chance of a young person engaging with an offender as their suspicions are lowered. Deception often involves the offender masquerading as a young person (Palmer & Stacey, 2004).…”
Section: Deceptionmentioning
confidence: 99%
“…Research has demonstrated that the media and personal experience/knowledge of crime plays an important role in shaping public perceptions of the crime problem (Davidson, 2008;Jewkes, 2004;Mohan, Twigg, and Taylor, 2011;Reiner, 2007). In particular, studies have evidenced the distortive effect of the tabloid media on public perceptions of sex crimes (Brayford & Deering, 2012;Farrell & Soothill, 2001;Greer, 2003;Jewkes, 2010;Kitzinger, 2004;Soothill & Walby, 1991;Thakker 2012). The protests following the controversial ''Name and Shame'' campaign of convicted sex offenders, spearheaded by a Sunday tabloid, the News of the World, demonstrate clearly the emotive public reaction to sex offending and sex offenders and subsequent calls for public disclosure (Silverman & Wilson, 2002).…”
Section: Public Perceptionsmentioning
confidence: 99%
“…In 2006, of those who were arrested for online solicitation 87% had actually targeted online undercover investigators. As yet there is little consensus about whether there are inherent properties of the Internet that encourage the commission of these offences or whether the use of technology has simply made them easier to detect (Jewkes, 2010;Jung, Ennis, & Malesky, 2012).…”
Section: Introductionmentioning
confidence: 96%